2016
DOI: 10.4110/in.2016.16.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Helper T (Tfh) Cells in Autoimmune Diseases and Allograft Rejection

Abstract: Production of high affinity antibodies for antigens is a critical component for the immune system to fight off infectious pathogens. However, it could be detrimental to our body when the antigens that B cells recognize are of self-origin. Follicular helper T, or Tfh, cells are required for the generation of germinal center reactions, where high affinity antibody-producing B cells and memory B cells predominantly develop. As such, Tfh cells are considered as targets to prevent B cells from producing high affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 123 publications
0
10
0
Order By: Relevance
“…Due to the observed increased proportion of T FH cells and the results of a previous study that showed enhanced B cell function in sheep RBC immunized mice (27), we hypothesized that there would be elevated levels of GC B cells. The inguinal lymph node cells were analyzed by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the observed increased proportion of T FH cells and the results of a previous study that showed enhanced B cell function in sheep RBC immunized mice (27), we hypothesized that there would be elevated levels of GC B cells. The inguinal lymph node cells were analyzed by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…T follicular helper (T FH ) cells, which express the CXCR5 and key transcription factor B-cell lymphoma 6 (Bcl-6), are localized in the GC in draining lymph nodes (25). T FH cells provide critical costimulatory signals and cytokines to B cell cognates, resulting in somatic mutation for affinity maturation and isotype-class switch (26272829).…”
Section: Introductionmentioning
confidence: 99%
“…B cell differentiation into autoantibody-secreting cells in these mice largely occurs at extrafollicular sites. Autoantibody production is supported by CD4 + T extrafollicular helper cells (T HEF ); these cells reside outside the B cell follicle and their gene expression profile resembles that of follicular helper T (T FH ) cells, although they express CXCR4 rather than CXCR54748. Yet, the mechanisms by which MSCs suppress B cell hyperactivity in MRL.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated B cell subpopulations were found in a variety of autoimmune diseases, such as IgG4related disease and primary Sjӧgren's syndrome (7). The production of high-a nity antibodies results from the interactions between B cells and T follicular helper (Tfh) cells; an increased number of circulating Tfh cells has been correlated with the severity of autoimmune diseases (8,9).…”
Section: Introductionmentioning
confidence: 99%